Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T14:19:44+01:00
A) -6,5 - (-2 1/4) + (-3 1/2 )- (-4,2) + [-(-4 3/4)]=
= -6,5+2,25-3,5+4,2+4,75 =
= 1,2

b)5,4 + (-1 1/5) - (-6,5) + (-3 1/4) -7,1 =
= 5,4-1,2+6,5-3,25-7,1 =
= 0,35

c) - {- [- (-3,5)] + [-(-4 1/4)] - [-(-3 1/3)]}=
= - { -3,5+4,25-3⅓} =
= 3,5-4,25+3⅓ =
= -¾+10/3 =
= 10/3 - ¾ =
= 40/12 - 9/12 =
= 31/12
2010-01-24T14:20:41+01:00
A) -6,5 - (-2 1/4) + (-3 1/2 )- (-4,2) + [-(-4 3/4)]=
-6,5+2¼-3½+4,2+4¾= -6½+2¼-3½+4⅕+4¾=-10+7+4⅕= 1⅕

b)5,4 + (-1 1/5) - (-6,5) + (-3 1/4) -7,1 = 5⅖-1⅕+6½-3¼-71/10=
-3i1/10+3¼=7/20

c) - {- [- (-3,5)] + [-(-4 1/4)] - [-(-3 1/3)]}=-(-(3,5)+(+4¼)-(+3⅓))=
-(-3,5+4¼-3⅓)=3,5-4¼+3⅓=-1¼+3⅓=2i7/12